Oxygen consumption of rats with broad intestinal resection - Luz, Jacqueline [UNIFESP] (2000)
The study was performed to investigate possible alterations in oxygen consumption in an animal model with broad intestinal resection. Oxygen consumption and the thermal effect of a short meal were measured in rats subjected to short bowel syndrome. Four groups of rats were used. Group I was the control group, group II was sham operated, group III was submitted to 80% jejunum-ileum resection, and group IV was submitted to 80% jejunum-ileum resection with colon interposition. Ninety days after surgery, oxygen consumption was measured over a period of 6 h with the animals fasted overnight. The thermal effect of feeding was determined in another session of oxygen consumption measurement in animals fasted for 12 h. A 12-kcal meal was then introduced into the animal chamber and oxygen consumption was measured for a further 4 h. No differences in fasting oxygen consumption or in the thermal effect of the meal were detected among the groups studied. It is concluded that short bowel syndrome does not affect the overall energy expenditure of rats.